2018
DOI: 10.1097/jsm.0000000000000507
|View full text |Cite
|
Sign up to set email alerts
|

Vision and Vestibular System Dysfunction Predicts Prolonged Concussion Recovery in Children

Abstract: Vision and vestibular problems predict prolonged concussion recovery in children. A history of motion sickness may be an important premorbid factor. Public insurance status may represent problems with disparities in access to concussion care. Vision assessments in concussion must include smooth pursuits, saccades, near point of convergence (NPC), and accommodative amplitude (AA). A comprehensive, multidomain assessment is essential to predict prolonged recovery time and enable active intervention with specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
122
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 136 publications
(129 citation statements)
references
References 39 publications
1
122
2
Order By: Relevance
“…Of course, 4 months likely represents a biased population seen in a concussion specialty clinic, so it may not represent the natural history of concussion. Although previous work has identified several prognostic factors for concussion recovery, 22,30,37,44 our results did not indicate that premorbid conditions, injury characteristics, or functional factors relate to symptom resolution time. This may be due to the fact that we focused only on sport-related injuries that were evaluated in a specialty care sports medicine clinic.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Of course, 4 months likely represents a biased population seen in a concussion specialty clinic, so it may not represent the natural history of concussion. Although previous work has identified several prognostic factors for concussion recovery, 22,30,37,44 our results did not indicate that premorbid conditions, injury characteristics, or functional factors relate to symptom resolution time. This may be due to the fact that we focused only on sport-related injuries that were evaluated in a specialty care sports medicine clinic.…”
Section: Discussioncontrasting
confidence: 99%
“…In patients evaluated within 14 days after injury, Master and colleagues found that balance deficits during tandem gait testing were associated with prolonged recovery. 30 Thus, balance deficits may be more readily predictive of prolonged recovery when tested sooner after injury (2 weeks in that study). Furthermore, our results suggest that almost all patients report symptom resolution within approximately 4 months after injury, which is valuable for clinicians to recognize as they provide counseling for patients regarding the expected duration of recovery.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Although most symptoms related to concussions resolve within 7 to 10 days, symptoms could last longer than a month significantly impacting academic performance. 59 Although concussion reportedly impacts the vestibular system [60][61][62][63][64] and vestibular rehabilitation is often prescribed for athletes with chronic concussion syndrome, 58,65 the studies that report vestibular system deficits in children with concussion do not directly measure the vestibular system using gold standard objective tests. Concussion diagnosis is, instead, based on symptom scales such as the vestibular oculomotor measurement scale.…”
Section: Concussionmentioning
confidence: 99%
“…Concussion diagnosis is, instead, based on symptom scales such as the vestibular oculomotor measurement scale. [60][61][62][63][64] Alshehri et al 66 showed no VOR deficit to the video head impulse test (vHIT) in 56 participants post-concussion, aged 10 to 20 years and determined that the vHIT test significantly increased symptoms of headache, dizziness, and nausea. Many of the intervention studies that reported the effectiveness of vestibular rehabilitation for patients with concussion are retrospective and not controlled.…”
Section: Concussionmentioning
confidence: 99%